Penile reconstruction - Garaffa, Giulio (Nature Publishing Group, 2013)
During the most recent years, a variety of new techniques of penile reconstruction have been described in the literature. This paper focuses on the most recent advances in male genital reconstruction after trauma, excision of benign and malignant disease, in gender reassignment surgery and aphallia with emphasis on surgical technique, cosmetic and functional outcome.